The Role and Value of Research Outputs in Coproducing Research With Communities - Jenny Barke (The University of Alabama, 2022)
Coproduced research aims to bring university researchers, community members, and organizations together to create new knowledge, share findings, and develop meaningful research outputs. While there is a growing body of work exploring the processes and methods of coproduction, little attention has been paid to the role and value of the outputs of coproduced research. This article addresses this gap in the literature by considering the value and role of a range of outputs developed via a coproduced community history research project. This article suggests that research outputs fulfill a number of key functions in addition to disseminating findings. Research outputs help collaborators make sense of a project and support the development of research skills and knowledge. Developing outputs also provides space to recognize individual interests and skills, build a collective vision, and help people recognize their own expertise. The article argues that research outputs are fundamental to the process of coproducing research, not simply its end result, and suggests that coproduced research outputs should be viewed as a site of research practice and knowledge production.